My Fish and I: Human-Fish Interactions in the 21st Century - Galhardo, Leonor (Journal of applied animal ethics research, 2021)
Abstract ‘My fish and I’ is an account of the diversity of human-fish interactions. This includes their benefits, detriments/harms as well as their moral and animal welfare. Fish are not easily perceived as individual animals having mental states, interests, needs and a degree of individuality. Additionally, fish have been handled as a simple resource in innumerable human interactions. Important ethical approaches address animal-human interactions based upon the individual’s cognitive ability and capacity to feel pleasure and pain. Given the ample evidence that fish have neuroanatomical structures that support the capacity to feel (sentience) and have complex behavioural and cognitive abilities, a moral duty is imposed upon us. Some human-centered and eco-centered moral views complement different perceptions of the nature of our relationship with fish. This occurs both at the individual level and as species or populations face a serious need for conservation. The concepts and assessments in the developments of animal welfare science provide ample basis for an evolution in the quality of human-fish interactions. However, many stakeholders must take part in this evolution. This is especially true as it concerns those areas of activity involving many individual fish and higher levels of suffering. Examples of these are aquaculture and commercial fisheries where there is much more at stake. Consumers will have the last word in this role, namely by reducing fish consumption.